Putative Role of Respiratory Muscle Training to Improve Endurance Performance in Hypoxia: A Review - Álvarez-Herms, Jesús; Julià-Sánchez, Sonia; Corbi, Francisco; Odriozola-Martínez, Adrian; Burtscher, Martin (Frontiers in Physiology, 2019)
Respiratory/inspiratory muscle training (RMT/IMT) has been proposed to improve the endurance performance of athletes in normoxia. In recent years, due to the increased use of hypoxic training method among athletes, the RMT applicability has also been tested as a method to minimize adverse effects since hyperventilation may cause respiratory muscle fatigue during prolonged exercise in hypoxia. We performed a review in order to determine factors potentially affecting the change in endurance performance in hypoxia after RMT in healthy subjects. A comprehensive search was done in the electronic databases MEDLINE and Google Scholar including keywords: “RMT/IMT”, and/or “endurance performance”, and/or “altitude” and/or “hypoxia”. Seven appropriate studies were found until April 2018. Analysis of the studies showed that two RMT methods were used in the protocols: respiratory muscle endurance (RME) (isocapnic hyperpnea: commonly 10-30’, 3-5d/week) in three of the seven studies, and respiratory muscle strength (RMS) (Powerbreathe device: commonly 2x30 reps at 50% MIP (maximal inspiratory pressure), 5-7d/week) in the remaining four studies. The duration of the protocols ranged from four to eight weeks, and it was found in synthesis that during exercise in hypoxia, RMT promoted 1) reduced respiratory muscle fatigue, 2) delayed respiratory muscle metaboreflex activation, 3) better maintenance of SaO2 and blood flow to locomotor muscles. In general, no increases of maximal oxygen uptake (VO2max) were described. Ventilatory function improvements (maximal inspiratory pressure) achieved by using RMT fostered the capacity to adapt to hypoxia and minimized the impact of respiratory stress during the acclimatization stage in comparison with placebo/sham. In conclusion, RMT was found to elicit general positive effects mainly on respiratory efficiency and breathing patterns, lower dyspneic perceptions and improved physical performance in conditions of hypoxia. Thus, this method is recommended to be used as a pre-exposure tool for strengthening respiratory muscles and minimizing the adverse effects caused by hypoxia related hyperventilation. Future studies will assess these effects in elite athletes.